Geo-spatial analysis of rainfall variability in Khyber Pakhtunkhwa Province, Pakistan - Dawood, Muhammad; Shirazi, Safdar Ali (Ecological Questions, 2022)
This paper explores geo-spatial analysis of rainfall variability in Khyber Pakhtunkhwa province, Pakistan. The concern region lies in the north-west of Pakistan and frequently faced the challenges of floods each year. This is an attempt to find out the rainfall trend and fluctuation which is one of the prime indicator of climate change. For this study, the daily rainfall data comprises of almost five decades (1975-2015). For achieving the study objectives, daily, monthly and mean annual rainfall data were analyzed using Mann-Kendall and Standard Deviation combined. Additionally, to further process the rainfall data spatio-statistically, GIS technology has been applied. The analysis specifies that a positive rainfall detected in the meteorological stations of Peshawar, Dir, Chitral, Drosh, Kakul and Saidu, whereas the moderate rainfall trend is detected in Cherat, Bannu, and Balakot. The remaining stations expressed no obvious trend, due to low time period of data.